2006
DOI: 10.3354/meps312057
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of diatoms and dinoflagellates to phytoplankton biomass in the NE Atlantic Ocean and the North Sea

Abstract: Sampling by the continuous plankton recorder (CPR) survey over the North Atlantic Ocean and the North Sea has enabled long-term studies of phytoplankton biomass. Analysis of an index of phytoplankton biomass, the phytoplankton colour index (PCI), has previously shown an increase in phytoplankton biomass in the NE Atlantic. In the current study, further investigations were conducted to determine the contribution of diatom and dinoflagellate cell counts to the PCI, their fluctuations over the last 45 yr and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 34 publications
5
18
0
Order By: Relevance
“…9) decreased towards the hyper-oligotrophic zone and increased towards the mesotrophic and eutrophic zones. This is in agreement with Leterme et al (2006) who showed that the dinoflagellate abundances increased with trophic status in the NE Atlantic Ocean. The observed increase in heterotrophic dinoflagellates contribution with depth is coherent with previous observations in the Equatorial Pacific (Chavez et al, 1990).…”
Section: Discussionsupporting
confidence: 93%
“…9) decreased towards the hyper-oligotrophic zone and increased towards the mesotrophic and eutrophic zones. This is in agreement with Leterme et al (2006) who showed that the dinoflagellate abundances increased with trophic status in the NE Atlantic Ocean. The observed increase in heterotrophic dinoflagellates contribution with depth is coherent with previous observations in the Equatorial Pacific (Chavez et al, 1990).…”
Section: Discussionsupporting
confidence: 93%
“…Such low abundances were found for some of the clusters identified in this study (NanoORG, MicroORG and Micro2 clusters for which the median abundance value was close to 30 cells cm −3 ), in agreement with concentrations observed in previous studies for the possibly related phytoplankton genus, as discussed below, i.e. cryptophytes (Buma et al, 1992), diatoms and dinoflagellates (Leterme et al, 2006). Previous comparisons between bench-top flow cytometry and remote sensing (Zubkov and Quartly, 2003) could technically not include the entire size range of nano-to microphytoplankton.…”
Section: Phytoplankton Community Descriptionsupporting
confidence: 92%
“…In particular, the CPR dataset (5,977 samples, Figure 1) recorded an abundance of 72 diatom species or taxa over the period 1998-2010, representing from 40 to 90% of the total microphytoplankton abundance in Summer (June-August) and Spring (March-June), respectively (Leterme et al, 2006). These diatoms are identified at a species or taxonomic level (one taxon could represent more than one species).…”
Section: In-situ Cpr Datamentioning
confidence: 99%
“…For this purpose, the CPR diatom database from the North Sea and the English Channel were used (Figure 1). Broadly, diatoms represent a dominant taxon in the North Sea, at least during part of the year, with an abundance contribution from 40 to 90% of total microphytoplankton (Reid et al, 1990;Leterme et al, 2006). Please note that here the term "dominant" has not the same meaning that the one used in PHYSAT (see definition n ‱ 6 in Supplementary Material).…”
Section: Introductionmentioning
confidence: 99%